Analisis Kuantitatif Pembangunan Desa Berbasis Lingkungan Terhadap Indeks Desa Membangun di Kabupaten Lombok Barat - Ety Kurniawati; Ibrahim Ibrahim; Nurhayati Nurhayati (Universitas Hamzanwadi, 2025)
Villages have a strategic role in supporting sustainable development goals, including environmental management. In West Lombok Regency, which is prone to disasters, environmental aspects are an important factor in assessing village independence through the Village Development Index (IDM). This study aims to analyze environmentally-based village development and the relationship between environmental, social, and economic resilience as the determinants of IDM. The method used is quantitative descriptive with secondary data from the NTB Province PMD Dukcapil Service and literature studies, as well as primary data through interviews with stakeholders. The analysis was carried out through observation and simple statistics. The results of the study show that the Social Resilience Index has the strongest influence on IDM compared to the other two indices. The Environmental Resilience Index has indicators that are still low, especially in the Disaster Response aspect, with 50 villages in the super priority category and 47 villages in the priority category. In contrast, the Environmental Quality indicator shows better achievements. There is a weak correlation between the Social and Economic Resilience Index, while no correlation was found between the other indices. This study emphasizes the importance of strengthening social and environmental aspects in village development strategies to achieve independent village status. Villages have formulated environmentally-based development activities in village planning documents, but activities are still routine and administrative. There is a need for a transformation of the village environmental development approach from merely fulfilling administrative obligations to solving environmental problems in a strategic and measurable manner.